Report of a Pilot Program Using a Milk-Free Ready-to-Use Therapeutic Food Made From Soya, Maize, and Sorghum to Treat Severe Acute Malnutrition. Issue 1 (March 2021) - Banda, Theresa; Chawanda, Khataza; Tsuchida, Wakako; Kathumba, Slyvester
Background: Globally, ready-to-use therapeutic food (RUTF) with peanut and milk as the primary source of protein is used to treat children having severe acute malnutrition (SAM). Valid Nutrition in collaboration with Ajinomoto Co., Inc has developed a nonmilk RUTF from soybean, maize, and sorghum (SMS-RUTF) and demonstrated its efficacy. Objective: To pilot SMS-RUTF in treatment of SAM within Community-Based Management of Acute Malnutrition (CMAM) program in Malawi, Africa. Methods and Findings: This was implemented from January to July 2018 and its performance was based on the SPHERE criteria and Ministry of Health CMAM guidelines. A total of 742 children were treated with SMS-RUTF. Of these, 94.5% (95% CI: 92.6-96.0) were successfully discharged to supplementary feeding program (SFP) with middle upper arm circumference (MUAC) ≥115 mm or directly to their homes with MUAC ≥125 mm; 3.6% (95% CI: 2.4-5.3) defaulted, 1.9 % (95% CI: 1.0-2.1) died, and 0.0% nonresponders. Analysis of 222 children who were discharged home with MUAC ≥125 mm gave a recovery rate of 88.3% (95% CI: 88.3-92.2), a defaulter rate of 6.8 % (95% CI: 3.8-10.9), a mortality rate of 1.3% (95% CI: 0.3-3.9), and a nonresponders rate of 1.8% (95% CI: 0.5-4.5). These outcomes exceed SPHERE minimum performance standards. The mean (standard deviation) length of stay of children discharged to SFP and discharged directly home were 42.0 (20.9) and 46.1 (21.1) days, respectively. These outcomes are within the recommended average duration of <60 days. Conclusion: The pilot CMAM program using SMS-RUTF recipe that contains no milk or peanuts achieved SPHERE minimum standards. Based on this evidence, SMS-RUTF should be encouraged for treatment of SAM in children between 6 and 59 months in routine CMAM programs in Malawi and globally.